2018
DOI: 10.1038/s41467-018-04752-1
|View full text |Cite
|
Sign up to set email alerts
|

A phosphorylation switch turns a positive regulator of phototropism into an inhibitor of the process

Abstract: Phototropins are light-activated protein kinases, which contribute to photosynthesis optimization both through enhancement of photon absorption when light is limiting and avoidance responses in high light. This duality is in part endowed by the presence of phototropins with different photosensitivity (phot1 and phot2). Here we show that phot1, which senses low light to promote positive phototropism (growth towards the light), also limits the response in high light. This response depends in part on phot1-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 47 publications
5
29
0
Order By: Relevance
“…Recent work has shown that PKS4 acts in conjunction with phot1 to reduce phototropic responsiveness at higher light intensities (Schumacher et al, 2018). PKS4 is phosphorylated by phot1 (Demarsy et al, 2012), and the accumulation of its phosphorylated form has been shown to delay phototropism (Schumacher et al, 2018). However, this occurs by a mechanism that does not affect NPH3 dephosphorylation (Schumacher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that PKS4 acts in conjunction with phot1 to reduce phototropic responsiveness at higher light intensities (Schumacher et al, 2018). PKS4 is phosphorylated by phot1 (Demarsy et al, 2012), and the accumulation of its phosphorylated form has been shown to delay phototropism (Schumacher et al, 2018). However, this occurs by a mechanism that does not affect NPH3 dephosphorylation (Schumacher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…PKS4 is phosphorylated by phot1 (Demarsy et al, 2012), and the accumulation of its phosphorylated form has been shown to delay phototropism (Schumacher et al, 2018). However, this occurs by a mechanism that does not affect NPH3 dephosphorylation (Schumacher et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike etiolated seedlings, which show high sensitivity to directional blue light, de-etiolated seedlings growing in full sunlight do not show a strong phototropic response (Goyal et al, 2016;Schumacher et al, 2018). However, LRFR, which is typical of shaded environments, enhances phototropism (Ballaré et al, 1992;Goyal et al, 2016).…”
mentioning
confidence: 99%
“…Unlike etiolated seedlings, which show high sensitivity to directional blue light, de-etiolated seedlings growing in full sunlight do not show a strong phototropic response (Goyal et al, 2016; Schumacher et al, 2018). However, LRFR, which is typical of shaded environments, enhances phototropism (Ballare et al, 1992; Goyal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%